DECISION-MAKING CAPABILITY AND PRODUCTIVITY OF ELEMENTARY SCHOOL TEACHERS IN CUARTERO - Denosta, Jona Mae P.; Vasquez, Michael B.; Begas, Samson (IDEAS: Journal of Management & Technology, 2024)
The decision-making capability of elementary school teachers is a complex and multifaceted process that encompasses a diverse range of choices, each which of with substantial implications for dynamics,   students outcomes and long-term academic success. This study aimed to determine the extent of decision-making capability and degree of productivity of 177 elementary school teachers in the district of Cuartero for the school year 2023-2024, with a specific focus on elements such as extra-personal, interpersonal, intrapersonal, and personal and work related. The study placed emphasis on the critical need to understand the relationship between decision-making and productivity. The study utilized a quantitative descriptive-correlational design in which data were collected through a researcher-made questionnaire and analyzed using IBM SPSS Statistics version 26, employing various statistical methods such as frequency, mean, t-test, f-test, and Pearson’s correlation. The findings showed high levels of decision-making capability across various dimensions and very high productivity among teachers. Socio-demographic factors like age, sex, and length of service didn't significantly affect decision-making or productivity, except for educational attainment. However, there was a significant relationship between decision-making capability and productivity of elementary school teachers in the district of Cuartero.